Bismuth‐Based Pervoskite as a High‐Performance Cathode for Intermediate‐Temperature Solid‐Oxide Fuel Cells. Issue 3 (21st January 2014) - Huang, Shouguo; Gao, Feng; Meng, Zheng; Feng, Shuangjiu; Sun, Xiaohong; Li, Yide; Wang, Chunchang
Abstract A new bismuth‐based perovskite cathode material, Bi0.5Sr0.5Fe0.8Co0.2O3−δ (BiSFC), showing not only low area‐specific resistance but also a low thermal expansion coefficient, exhibits excellent electrochemical catalytic activity for the oxygen reduction reaction in the application of intermediate‐temperature solid‐oxide fuel cells (ITSOFCs). The high performance implies that BiSFC is a very promising cathode material for ITSOFCs.